Pemanfaatan Limbah Kotoran Sapi sebagai Energi Biogas Terbarukan: Program Pemberdayaan bagi Warga Binaan di Lembaga Pemasyarakatan Kelas I Malang - Febiola Sabrina; Fadhil Arifiyan Ekaputra; Sigit Dwi Kurniawan; Tasya Lifiana; Randika Akbar Faariz Afandi; Raihan Wahyu Pratama; Tri Wahyu Hardaningrum (STIKes Ibnu Sina Ajibarang, 2025)
The correctional facility SAE L’SIMA in Malang is confronted with two major challenges: the environmental impact of accumulated cow manure and the need to provide meaningful vocational training for inmates to support rehabilitation and reintegration. This community service program was designed to address both issues simultaneously through the introduction and application of biogas technology. The primary objective was to manage livestock waste as an alternative renewable energy source while equipping inmates with practical technical skills applicable beyond the correctional setting. The implementation method employed a participatory approach that involved several stages, including program socialization, site survey, biogas unit design, assembly of a small-scale digester, and subsequent monitoring and evaluation.The results demonstrated that the biogas unit was successfully constructed and operational; however, gas production levels remained below optimal standards. Key challenges identified included unstable temperature conditions, which negatively affected the fermentation process, and technical problems such as leakage in the piping system. These obstacles limited the overall effectiveness of gas generation. Despite these limitations, the project provided significant outcomes. First, it created a working model of sustainable energy generation within the correctional environment. Second, it delivered valuable vocational training for inmates, offering them both theoretical knowledge and hands-on experience in renewable energy technology. Furthermore, the program encouraged inmate participation, fostering teamwork, responsibility, and problem-solving skills that are essential for personal development.In conclusion, although technical barriers remain, this initiative succeeded in establishing the foundation for sustainable waste management and renewable energy application within a correctional facility. More importantly, it highlights the potential of biogas technology not only as an environmental solution but also as a rehabilitative vocational training tool. Continued monitoring, process optimization, and technical refinements are essential for achieving long-term success and scalability of this model in similar institutional contexts.